2005
DOI: 10.1080/09540120412331299807
|View full text |Cite
|
Sign up to set email alerts
|

AIDS-related discrimination in Asia

Abstract: The Asia Pacific Network of People Living with HIV/AIDS (APN+) conducted the first regional documentation of AIDS-related discrimination in Asia. This project was an action-based, peer-implemented study that aimed to develop an understanding of the nature, pattern and extent of AIDS-related discrimination in several Asian countries. Trained HIV-positive people interviewed 764 positive people in four countries (India 302; Indonesia 42; Thailand 338; the Philippines 82) using a structured questionnaire. Findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
163
0
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(177 citation statements)
references
References 28 publications
9
163
0
5
Order By: Relevance
“…However, similar to the findings for other Asian countries (Thailand, Philippines, Indonesia), the proportion of positive people reporting enacted stigma (personal experience of stigma or discrimination) is not very high in India (Paxton et al, 2005;Steward et al, 2008). Between 5 and 30 per cent of HIV positive Indian respondents in Paxton's study of PLHA in Asia reported discrimination (enacted stigma): 30% experienced discrimination by health workers, 20% were refused treatment by a health worker because of HIV status, and 15% were forced to pay additional charges for medical services on account of HIV status.…”
Section: Article Originalsupporting
confidence: 69%
See 2 more Smart Citations
“…However, similar to the findings for other Asian countries (Thailand, Philippines, Indonesia), the proportion of positive people reporting enacted stigma (personal experience of stigma or discrimination) is not very high in India (Paxton et al, 2005;Steward et al, 2008). Between 5 and 30 per cent of HIV positive Indian respondents in Paxton's study of PLHA in Asia reported discrimination (enacted stigma): 30% experienced discrimination by health workers, 20% were refused treatment by a health worker because of HIV status, and 15% were forced to pay additional charges for medical services on account of HIV status.…”
Section: Article Originalsupporting
confidence: 69%
“…In terms of geographical coverage, a Original Article majority of the studies are understandably carried out in regions with higher HIV prevalence (N=15): Tamil Nadu 8, Karnataka 3, Maharashtra 2 (1 rural site), Andhra Pradesh 1, rural Southern India 1. Four studies are designed as multisite studies in high, medium and low HIV prevalence states (Bharat et al, 2001;Paxton, Gonzales, Uppakaew, Abraham, Okta, Green et al, 2005;National AIDS Control Organization NACO b, 2006;Kurien, Thomas, Ahuja, Patel, Shyla, Wig, Mangalani, et al, 2007). Other study sites are located in lower HIV prevalence states of New Delhi (7), Kerala (1), and West Bengal (2), rural India (1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dans de nombreux pays où la discrimination envers les personnes vivant avec le VIH prévaut sur la « banalisation », notamment ceux qui ont été touchés récem-ment par l'épidémie, les professionnels de santé ne répondent pas aux demandes d'information ou de soutien en matière de procréation, et condamnent, voire maltraitent, les personnes qui prennent le risque d'avoir un enfant en se sachant séropositi-ves. En Asie du Sud-Est, de nombreux professionnels de santé proposent ou imposent aux femmes séropositives des mesures contraceptives définitives, telles que la stérilisation associée à une interruption de grossesse, dès la découverte de leur séro-positivité, mêmes si elles n'ont pas encore eu d'enfant [8,9]. Là où les femmes vivant avec le VIH reçoivent une information pré-ventive en matière de santé reproductive, celle-ci est généra-lement focalisée sur la prévention de la transmission du VIH, et la procréation n'est abordée que sous l'angle de la contraception ; l'indication du préservatif comme méthode commune aux deux objectifs, qui a pour effet la simplification de l'approche, contribue probablement à cette situation.…”
Section: En France Et Ailleursunclassified
“…I l était alors presque inconcevable qu'une femme séropositive connaissant son statut sérologique décide d'avoir un enfant, compte tenu de l'importance présumée du risque de transmission 8 . Cet excès de risque présumé transparaît dans les chiffres cités, supérieurs à ceux scientifiquement validés à l'époque : cette différence peut être considérée comme le résultat d'une amplification a posteriori due aux errements de la mémoire ou comme le reflet du discours médical réellement tenu 9 . Lorsque les femmes découvraient leur séropositivité pendant la grossesse, l'interruption de grossesse « allait de soi » si le diagnostic était établi au cours des premiers mois ; s'il l'était plus tardivement, certaines grossesses étaient menées à terme, notamment du fait des obstacles administratifs à la pratique d'une interruption 10 .…”
Section: En France Et Ailleursunclassified